2005
DOI: 10.1097/00005176-200505000-00085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breast-Feeding on Risk of Coeliac Disease: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background: Coeliac disease (CD) is a disorder that may depend on genetic, immunological, and environmental factors. Recent observational studies suggest that breast feeding may prevent the development of CD. Aim: To evaluate articles that compared effects of breast feeding on risk of CD. Methods: Systematic review and meta-analysis of observational studies published between 1966 and June 2004 that examined the association between breast feeding and the development of CD. Results: Six case-control studies met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 12 publications
(17 reference statements)
0
45
0
13
Order By: Relevance
“…Tables to summarise the characteristics of the included studies. In addition to the previously identified 12 studies, 9 new publications were identified, including three RCTs described in four publications . Two publications described the same population at different time points.…”
Section: Resultsmentioning
confidence: 99%
“…Tables to summarise the characteristics of the included studies. In addition to the previously identified 12 studies, 9 new publications were identified, including three RCTs described in four publications . Two publications described the same population at different time points.…”
Section: Resultsmentioning
confidence: 99%
“…CD has a multifactorial aetiology, but still the environmental and life‐style contribution is largely unexplored, besides studies on infant feeding. There is ample evidence that ongoing breastfeeding at the time of gluten introduction reduces CD risk in children younger than 2 years of age (3,4). The duration of this protection is not clear, but the gap in CD risk at 6 years of age, between Swedish birth cohorts differing with respect to infant feeding, supports a long‐term preventive effect (5).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, breastfeeding duration had increased. These changes resulted in a larger proportion of children gradually introduced to gluten while still breastfed, a pattern suggested reducing CD risk (3,4). Hence, birth cohorts of the epidemic and postepidemic periods differ with respect to infant feeding, and the gap in CD risk between such birth cohorts was still striking at 6 years of age, the longest follow‐up so far available (5).…”
Section: Introductionmentioning
confidence: 99%
“…[4] As for breast feeding, infants who are breast-fed at the time of gluten introduction and beyond are less likely to The recent availability of sensitive and specific serologic tests develop celiac disease later in life. [5] Finally, there is evidence that has now made it possible to assess the true prevalence of celiac repeated rotavirus infections are more frequent in children later disease, as such tests are able to detect cases with the typical who later go on to develop 'celiac disease autoimmunity' than in mucosal changes that are minimally symptomatic, or even asympmatched controls, [6] thus suggesting that such infections may set tomatic. We have therefore learned from screening studies that the stage for later development of celiac disease.…”
mentioning
confidence: 99%
“…All rights reserved.Mol Diag Ther 2008; 12(5) Risk Assessment, Diagnosis, and Monitoring of Celiac Disease…”
mentioning
confidence: 99%